The Decomposition Theorem for a Fuzzy Quasinorm - Rui Gao; Xinxin Li; Jianrong Wu (Journal of Mathematics)
This paper deals with fuzzy quasinormed spaces in the sense of Alegre and Romaguera. After introducing the concept of the family of star quasiseminorms, we prove the decomposition theorem for a fuzzy quasinorm with general t-norm, characterize fuzzy quasinorms in terms of families of star quasiseminorms, and establish the connection between the fuzzy quasinorm and the family of quasinorms.